Exploring corrosion protection properties of solvent based epoxy-graphene oxide nanocomposite coatings on mild steel. (1st February 2017) - Pourhashem, Sepideh; Vaezi, Mohammad Reza; Rashidi, Alimorad; Bagherzadeh, Mohammad Reza
Graphical abstract: Highlights: Epoxy- graphene oxide (GO) nanocomposite coatings are prepared successfully. GO significantly improves corrosion resistance and adhesion of epoxy coatings. The viscosity of polymer matrix has great effect on GO dispersion quality. The effect of GO dispersion quality on corrosion resistance is studied. Nanocomposite coatings with different GO wt.% show different corrosion resistance. Abstract: Solvent-based epoxy coatings filled with graphene oxide nanosheets (GO) are developed to enhance the corrosion protection of mild steel substrates. Results reveal that GO distribution in polymer matrix is the most important parameter influencing coating performance. Viscosity of polymer matrix and GO weight percent (wt.%) are exceptional aspects for GO dispersion quality. Among nanocomposites prepared with different methods and GO wt.% (0.05, 0.1, 0.3, and 0.5), coatings prepared via direct addition of 0.1 wt.% GO to polymer matrix with lower viscosity show desirable GO dispersion quality, better adhesion to substrate, outstanding barrier properties and superior corrosion protection under NaCl electrolyte.